2011
DOI: 10.1016/j.msea.2010.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure development and hardening during high pressure torsion of commercially pure aluminium: Strain reversal experiments and a dislocation based model

Abstract: The effect of strain reversal on hardening due to high pressure torsion (HPT) was investigated using commercially pure aluminium. Hardening is lower for cyclic HPT (c-HPT) as compared to monotonic HPT (m-HPT). When using a cycle consisting of a rotation of 90° per half cycle, there is only a small increase in hardness if the total amount of turns is increased from 1 to 16.Single reversal HPT (sr-HPT) processing involves torsion in one direction followed by a (smaller) torsion in the opposite direction. It is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 54 publications
0
40
0
Order By: Relevance
“…Grounding increases microhardness of the as-cast Mg to about 42 Hv and increasing turns of HPT do not further increase its hardness, which is very different from most HPT processed FCC metals and alloys for which the microhardness generally increases with the equivalent strain until strain of 3 (see e.g. [5,8,19]). Furthermore, microhardness across the diskshaped sample is not homogeneous and it does not show any dependency on the distance from the disk edge to the centre although different positions on the disk experience different deformation (shear strain is proportional to the distance [19]).…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…Grounding increases microhardness of the as-cast Mg to about 42 Hv and increasing turns of HPT do not further increase its hardness, which is very different from most HPT processed FCC metals and alloys for which the microhardness generally increases with the equivalent strain until strain of 3 (see e.g. [5,8,19]). Furthermore, microhardness across the diskshaped sample is not homogeneous and it does not show any dependency on the distance from the disk edge to the centre although different positions on the disk experience different deformation (shear strain is proportional to the distance [19]).…”
Section: Methodsmentioning
confidence: 73%
“…[5,8]). For instance, as shown in disk centre, the hardness increases with the equivalent strain [ 19 ], and eventually becomes saturated. Further processing causes drop of hardness due to recovery (not shown in Fig.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…9 shows the variation of microhardness with the imposed equivalent strain. The equivalent strain is expressed as [10,31,32]:…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al [14] found that the dislocation density in the grain interior decreased by 60% after annealing. Zhang et al [15] found that the residual dislocation density in an HPT-processed pure aluminum sample after annealing was about 7×10 found that the microstructure of the 20% whisker sample before heating is characterized by small subgrain size (2 to 3 m) and by a residual dislocation density of about 10 In this letter, we report the fabrication of Al/Ti/Al laminate foils by asymmetric rolling, followed by annealing at 873K for up to seven days. We found an abnormally high residual dislocation density in the pure aluminum zone.…”
Section: Introductionmentioning
confidence: 82%